Transparency and documentation : lessons in accountability from British police - Morrell, Kevin (London : SAGE Publications: SAGE Business Cases Originals, 2020)
This case introduces one way in which police officers in Britain are made accountable for their decisions. It focuses on the requirement for police officers to record decisions in "pocketbooks"—notebooks that document the basis for important decisions. These records (taken at the time or as soon as possible afterwards) can become public because they may be scrutinised in court. This documentation is intended to make the basis for decisions transparent in so that individual officers are held accountable and to support prosecution. The case uses this setting as a jumping off point to consider whether corporate accountability could be improved through greater use of documentation. Should CEOs be required to record their most important decisions (which can perhaps lead to redundancies or other kinds of harm) in a similar way?
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Social responsibility of business -- Case studies; Business enterprises -- Documentation -- Case studies